Integrated multi-scale water management as a climate change adaptation strategy - Tan, Raymond Girard R. (Animo Repository, 2018)
Water management will become increasingly critical as the effects of climate change manifest. There are existing water management tools and concepts in current use for both policy and decision-making in industry, but these often look at water issues from the limited perspectives of specific decision-makers who see the problems only at particular scales. In this perspective paper, we argue for an integrated water management approach as an imperative climate change adaptation; there is an urgent need for research on the development of such a multi-scale framework to effectively manage water use in industrial systems. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.